Corporate Governance and Environmental Disclosure: Assessing The Role of Environmental Performance - Itan, Iskandar; Laudeciska, Leni; Karjantoro, Handoko; Chen, Robin (Universitas Muhammadiyah Surakarta, 2023)
This research aims to examine and provide empirical evidence of the influence of Corporate Governance on Environmental Disclosure, with Environmental Performance as a mediating variable. The study was conducted on publicly traded companies that disclosed Corporate Social Responsibility during the period from 2018 to 2021 and participated in PROPER (Program for Environmental Performance Rating and Disclosure). The sample was determined using purposive sampling and consisted of 61 companies. The results of the research show that Corporate Governance is positively related to environmental performance and disclosure. The findings also indicate that environmental performance partially mediates the relationship between corporate governance and the quality of environmental disclosure.